Elements of vogue : un caso de estudio de performance radical - Gavaldon, Sabel; Segade, Manuel (Madrid : CA2M, 2019)
Charles Atlas, Dawoud Bey, Joan Jett Blakk, David Bronstein, Willie Cole, Emory Douglas, LaToya Ruby Frazier, Ellen Gallagher, Bam Bam Garçon, Gerard H. Gaskin, Lyle Ashton Harris, Benji Hart, Juliana Huxtable, Arthur Jafa, Marsha P. Johnson, D’relle Khan, Crystal LaBeija, Zoe Leonard, Glenn Ligon, Kalup Linzy, L.O.V.E. Lesbians Organized for Video Experience, Dorothy Low, Paul Maheke, MikeQ, Rashaad Newsome, Lorraine O’Grady, Paper Tiger Television, Adrian Piper, Carl Pope Jr., Pope.L, Qween Beat, Jay Jay Revlon, Marlon T. Riggs, Sylvia Rivera, Martha Rosler, Stephen Shames, Frank Simon, Lorna Simpson, Bruce W. Talamon, Terre Thaemlitz, Wu Tsang, James Van Der Zee, Jack Walworth, Andy Warhol, Cornel West, Ernest C. Withers
This notion of radical performance is what defines voguing, a popular culture that unfolds around transgender pageants and spectacular dance battles between queens of Black and Latino descent. Vogue is a defiantly queer dance style, the roots of which go deep down into the history of the African diaspora. It draws inspiration from the poses in top women’s fashion magazines, re-appropriating the elitist imaginary of haute couture and combining it with the vocabulary of Egyptian hieroglyphs, Asian martial arts and Afrofuturism. Such a transgender, multicultural hallucination is what made vogue emblematic of a fiercely underground scene: namely, the ballroom scene. Ballroom culture flourished in 1980s New York as a response to the AIDS crisis, but its history spans a century of fragile coalitions between minorities that have been consigned to the margins, incarcerated and pathologised throughout the modern period. In the stylised poses of voguing, the dancer’s hands do more than just draw figures in the air. These poses are a bodily transcription of a history of resilience that can be traced back to the 1920s, coinciding with the first massive drag balls of the Harlem Renaissance. With its elaborate rules, aesthetic codes and forms of social organisation, ballroom culture is still a platform to channel queer energies and affirm the lives of nonconforming bodies in what constitutes a case study of radical performance.
Catalogus bij de tentoonstelling onder andere te Madrid (CA2M Centro de Arte Dos de Mayo) van 17 november 2017 tot 6 mei 2018
boek
Keywords: Homoseksualiteit; Transgender